Curcumin ameliorates pulmonary fibrosis progression by inhibiting the fibrotic process of lung fibroblasts: Curcumin inhibits pulmonary fibrosis - Qiao, Man; Li, Dongsheng; He, Yuan; Cui, Qingming; Chi, Hang; Li, Xiaoqiu; Li, Shaoying; Jiao, Ying; Wei, Xuan (Cellular and Molecular Biology, 2023)
The objective of this study was to analyze the effect of curcumin (Cur) on pulmonary fibrosis (PF), so as to provide new clinical evidence for future PF treatment. To achieve these goals, the researchers set up bought human lung fibroblasts MRC-5 as a control group without treatment, a model group for PF cell modeling, and an intervention group for Cur intervention after PF modeling. Cell proliferation capacity and cellular TGF-β1, α-SMA, Collagen I, Collagen III, Bax, N-cadherin and E-cadherin protein expression were determined. The results show that markedly enhanced cell proliferation capacity and TGF-β1, α-SMA, Collagen I and Collagen III protein levels were observed in the model group, while the cell activity and fibrosis degree in the intervention group were significantly decreased compared with the model group (P<0.05). In addition, the intervention group exhibited lower N-cadherin and Bax with higher E-cadherin than the model group (P<0.05). In addition, the team found that the inflammatory response and oxidative stress were also more significantly improved in the intervention group (P<0.05). These experimental results tell us that Cur can ameliorate the fibrotic process of PF by inhibiting the activity of MRC-5.